Is AD a Stress-Related Disorder? Focus on the HPA Axis and Its Promising Therapeutic Targets - Canet, Geoffrey; Hernandez, Célia; Zussy, Charleine; Chevallier, Nathalie; Desrumaux, Catherine; Givalois, Laurent (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s Disease (AD) is a progressive neurodegenerative disorder that has important health and economic impacts in the elderly. Despite a better understanding of the molecular pathogenesis mechanisms leading to the appearance of major pathological hallmarks of disease hallmarks (senile plaques and neurofibrillary tangles), effective treatments are still lacking. Sporadic AD forms (98% of all cases) is aare multifactorial pathology, and its complexity could be explained by a panoply of risk factors have been identified. While tThe major risk factor is aging, but growing evidences suggests that chronic stress or stress-related disorders increase the probability to develop AD. In patients, Aan early dysregulation of the hypothalamic-pituitary-adrenal axis (HPA axis or stress axis) has been was observed in patients. The direct consequence of such perturbation is an oversecretion of glucocorticoids (GC) over-secretion associated with a an impairment of its receptors (GR)impairment. These steroids hormones easily penetrate the brain and act in synergy with excitatory amino acids. An overexposure could be highly toxic in limbic structures (prefrontal cortex and hippocampus) which and could contribute participate at term to the cognitive decline occurring in AD. GC and GR dysregulations seem to be involved in lots of functions disturbed in AD and there is the installation of a vicious cycle appears, where AD induces the dysregulation of the HPA axis dysregulation, which in turn potentiates the pathology. This review presents some preclinical and clinical studies focusing on the HPA axis hormones and their receptors to fight against AD. Due to its primordial role in the maintenance of homeostasis, the HPA axis could appears as a key-actor in the etiology of AD and a prime target to tackle AD by offering multiple angles of action.